MODERN STRUCTURE OF THE URALS AS A RESULT OF THE POST-PALEOZOIC EXTENSION OF THE EARTH'S CRUST - Ivanov K.S. (My University, 1998)
The Urals structure, as a whole, is the result of the post-Permian sublatitudinal extension of the region. It is characterized by alternating submeridional zones: synform zones made up of nonmetamorphosed volcanogenic and sedimentary series and the antiform ones comprised of deep metamorphic and intrusive complexes. The boundaries between these zones are large faults, which usually descend at angles of 30-50° to less metamorphosed rocks. These faults are mainly normal faults which appeared as a result of the Earth's crust extension, but not overthrusts, as was considered earlier. These young faults developed primarily in tectonically weak zones of the older thrusts and detachment zones which were present between the upper (brittle) and middle (plastic) crust. Exhumation of megablocks of the high-grade rocks formed in the lower and middle crust occurred as a result of their uprise to the upper crust during the rupture and extension of the latter. The extension began, evidently, in the Early Triassic. The South Urals structure along the Kumertau-Nikolaevka profile is described. A new important tectonic stage - post-collision extension - has been determined in the geological history of the Urals.
Keywords: Paleozoic; Paleozoic; Палеозой